Photosynthetic activity in avocado leaf ontogeny as a result of compatibility rootstock/scion in three locations in Colombia - Cano-Gallego, Lucas Esteban; Bernal-Estrada, Jorge Alonso; Hernández-Arredondo, Juan David; Correa-Londoño, Guillermo Antonio; Córdoba-Gaona, Oscar de Jesús (Revista Ceres, 2024)
In Colombia, the evidence of rootstock/scion incompatibility in avocado cv. Hass graft union has been increasing, generating concern among farmers. The objective was to evaluate the photosynthetic response of the avocado trees due to rootstock/scion compatibility in three locations. A split plots design with a blocking factor per locality was used. The main plot corresponded to the type of graft union (compatible and incompatible) and the subplots to leaf age during the 2020 and 2021 seasons. Climatic (water balance) and gas exchange variables (photosynthesis, transpiration, stomatal conductance, leaf temperature, and efficiency in instantaneous water use) were measured. The results indicate that the photosynthetic performance was not affected when the water balance was negative. Compatibility did not significantly affect gas exchange variables (A, gs, E, Tl, and WUEi) during the main and secondary harvest period. The leaf age/harvest period interaction shows that during the first months of leaf development, A, gs, E, and Tl are greater and are detrimental over time. It is concluded that the rootstock/scion compatibility does not significantly modify the capacity to assimilate CO2. At the same time, the variation in avocado photosynthetic activity depends on the age of the leaves and the harvest season.